Adapted public space – an innovative place of entertainment and integration - Magdziak, Monika (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
The purpose of the work is to illustrate a number of ways of creating or revitalizing urban spaces to build the identity and image of the city, but also to integrate the fragments and utilize the potential of urban wasteland. The aspect of space users themselves is also signifi cant – as they are the initiators, organizers and participants in the process of reating public space. In this paper, the author focuses on the importance of alternative ways of adapting space and creating spatial and social relationships. The design goal should be based on the needs and preferences of different groups of people and use real spatial resources. The author discusses issues of activating space and residents through architectural forms, cultural activities and participatory actions. The aim was to show the impact and benefi ts of bottom-up social initiatives, temporary spatial interventions, as well as pro-ecological activities, as effective methods of restoration of urban landscape in a short time and at low cost.